Changing the Beat: Fostering the Prevention of Alcohol-Related Violence in Nighttime Leisure Zones. (June 2016) - Perez-Trujillo, Monica; Reyes, Maria-Fernanda; Cabrera, Lady; Gomez, Augusto Perez
Opportunities for crime are related to specific times and places. However, studies on alcohol-related violence have mostly focused on the role of neighborhood-level factors over large areas and long periods of time, meaning that we know surprisingly little about how people's interactions with the environment at specific times and places affect alcohol-related violence. In order to explore opportunities for violence in public places with high alcohol outlet densities, we conducted a multiple case study of two nighttime leisure microenvironments in Bogota, Colombia. Based on more than 150 hrs of participant observation in each site during nighttime activity over 4 months, we characterized each setting in terms of physical risk factors, actor heterogeneity, incidents of aggression, alcohol use dynamics and routines, and the intervention of different types of guardianship in these contexts. Results show that, despite similarities in the physical characteristics of the environment and alcohol availability, there are important differences in place-based dynamics that increase or decrease opportunities for violence and crime. We discuss how our results contribute to the development of opportunity theories and conclude with policy implications and opportunities for intervention.